TREATMENTS OF CLASS III SEVERE CROWDED TEETH WITH DAMON BRACKET SYSTEM: EXTRACTION VS NON EXTRACTION: PERAWATAN GIGI GELIGI BERLAPIS KELAS III DENGAN SISTEM BRAKET DAMON: DENGAN DAN TANPA PENCABUTAN GIGI (Dentika: Dental Journal, 2011)
One of a self-ligating bracket is Damon bracket system, most is the blending of passive self-ligating brackets and hightechnology archwires. Damon bracket system usually needs the absence of teeth extraction for treatment but in some Asian cases the treatment still need to extract teeth. Recently, more recognized that the othodontic treatment goals shifted from dentition to facial esthetic, not only the convexity of facial esthetic, but also how to create a nice smile arc. This case report presents two treatments of mild Class III severe crowded teeth with Damon bracket system, the extraction case and the non extraction case. The first case, female patient, 17 years old, had 0,5 mm overjet and 1 mm overbite. Both first premolars maxilla and mandibular had been extracted. The second case, female patient, 13 years old, had - 4 mm overjet and 3 mm overbite, none of teeth had been extracted. High torque Damon bracket system slot 0.022â€ was applied to the first patient and low torque with slot 0.018â€ to the second patient. Class III dental relationship was corrected with a positive overbite, overjet and good occlusion was achieved for both patients within 17 months. There were no more crowding teeth, profile is also improved. In conclusion, damon bracket system was given the fast and painless treatment with longer time interval of controls.